Hislopathalogical Changes in the Testes and Epididymis of Mice Fed with Cadmium Chloride - Kadhim, A.H.; Al-Bairuty, J.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present research was conducted to determine the effect of Cadmium Chlori de on the t stes and epididymis of white mice fed with diffl rent concentration (75, 1 00 150 ppm) of this hea y metal for three, ix and nine days. The r ults showed that cadm i um chloride caused s vera! histopathalogical change in testes and epidid mis in luding deg neration and cell necrosis in addition to the appearanc of haemorrhage and o dema in the tissues . It was clear that the effect increased in r lation with the concentration and the treatment period.